(untitled) (Journal of Philosophy Culture and Political Science, 2026)
The study of national costume is a topical task in the context of preserving cultural traditions and adapting them to modern times. The article provides a research analysis of the history of national clothing, reveals the artistic and compositional principles of its organization and aesthetic solution. The ethno-traditional features of the evolution of national costume as an exceptional type of arts and crafts, as well as methods of integrating national motifs into modern fashion are considered. The scientific concept of "national costume" is defined and the following terms are differentiated: "folk costume", "ethnic costume", "traditional costume". The need for a comprehensive interdisciplinary study of ethnic costume, its role in the formation of ethnocultural identity, intercultural communication and ideological attribution of the nation is substantiated. The functional and semiotic polysemy of clothing, as well as its significance in the social structure of society, are analyzed. Key words: National costume, traditional costume, evolution of costume, ethnocultural identity, intercultural communication, arts and crafts, semiotics of clothing, ideological attribution. Key words: National costume, traditional costume, evolution of costume, ethnocultural identity, intercultural communication, arts and crafts, semiotics of clothing, ideological attribution.